The Need for Creation of a Cluster of Pedagogical Innovations in the System of Continuous Education - Khaytboy Eralievich, Sultanov; Izzat Mukhamatsultonovna, Marasulova; Ilkhomjon Saidazimovich, Bakhriev; Rahim Turgunovich, Ankabaev (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the need for modern changes in the market of modern educational services in the country and new innovative technologies and analyzes the concept of “education cluster” and identifies the role of higher education in it. It is concluded that the development of the cluster as a mechanism of innovative management of the general education system will ensure the effectiveness of the activities of each educational institution included in it. The main problems of the formation of training clusters and ways to solve them are identified. It also looks at the formation of “school-laboratory” innovative research platforms that provide a link between the educational process and practice in the field of fine arts.